Hepatic Artery Infusion Chemotherapy in Hepatoma. Issue 5614 (10th August 1968) - Provan, J. L.; Stokes, J. F.; Edwards, D.
Abstract : Three patients with inoperable malignant hepatomas were treated by intra-arterial infusion of fluorouracil. In each case the treatment gave relief of symptoms: there was striking relief of pain in two cases. Preoperative angiography is essential, but the technical problems are relatively minor. The response of the tumours to chemotherapy is sufficiently encouraging to justify greater efforts for early diagnosis.